2013
DOI: 10.1080/02643944.2013.861506
|View full text |Cite
|
Sign up to set email alerts
|

Circle time for social and emotional learning in primary school

Abstract: This paper discusses the findings and implications of a semi-randomised control trial study on the effectiveness of circle time (CT) on primary school students' social and emotional learning, as well as classroom teachers' and students' experience of CT. A social and emotional learning programme was delivered through CT by trained classroom teachers across the years in one primary school, with other classrooms serving as control groups. The classroom teachers completed the Strengths and Difficulties Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
5
20
0
1
Order By: Relevance
“…For example, classroom observations indicated that classroom-based assessment during the teaching and learning process was often done in the fashion and format of the end of cycle examinations, PLE which assesses only traditional quantifiable knowledge and skills. This disagrees with Cefai et al (2014) who argued that assessment should be widened to include a broader educational agenda, integrating the person's physical, social, emotional, artistic and spiritual development which Gardner (1983) termed as a person's multiple intelligences. Cefai et al (2014) further argued that assessment should consider the individual's readiness for the world of work, or life beyond school to embrace the ability of learners to navigate life in the 21 st century.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, classroom observations indicated that classroom-based assessment during the teaching and learning process was often done in the fashion and format of the end of cycle examinations, PLE which assesses only traditional quantifiable knowledge and skills. This disagrees with Cefai et al (2014) who argued that assessment should be widened to include a broader educational agenda, integrating the person's physical, social, emotional, artistic and spiritual development which Gardner (1983) termed as a person's multiple intelligences. Cefai et al (2014) further argued that assessment should consider the individual's readiness for the world of work, or life beyond school to embrace the ability of learners to navigate life in the 21 st century.…”
Section: Discussionmentioning
confidence: 97%
“…This disagrees with Cefai et al (2014) who argued that assessment should be widened to include a broader educational agenda, integrating the person's physical, social, emotional, artistic and spiritual development which Gardner (1983) termed as a person's multiple intelligences. Cefai et al (2014) further argued that assessment should consider the individual's readiness for the world of work, or life beyond school to embrace the ability of learners to navigate life in the 21 st century. This readiness for work would call for assessing the levels of learners' academic, social and emotional literacy.…”
Section: Discussionmentioning
confidence: 97%
“…Mosley, who "placed emphasis on the dimension of problem solving and decision-making for the circle" (Lown, 2002, p. 95), shares McAfee's views. In studying the effects of applying circle time to cognitive learning, scholars have developed detailed and extensive training programs along with systematic evaluation approaches to measure results (Cefai et al, 2014;B. Collins, 2013;Lown, 2002;Miller & Moran, 2007;Mosley, 1999;Tew, 1998).…”
Section: Literature Review: Academic Discourse On Circle Timementioning
confidence: 99%
“…With compelling evidence that psychosocial characteristics are vital to children's overall academic and behavioural functioning, researchers have sought to examine the ways through which teachers can address students' social-emotional development needs in the classroom. Circle time, as it has been referred to in schooling contexts, has been promoted to be a promising practice to address students' social-emotional development (e.g., Boyes-Watson & Pranis, 2014;Cefai, Ferrario, Cavioni, Carter, & Grech, 2014). A circling approach can be best described as an intentional communication process that is student-centered and focused on helping students to: build and restore healthy relationships, develop skills to solve social problems, build self-esteem, and support cooperative classroom environments (Hennessey, 2007;Riestenberg, 2012).…”
mentioning
confidence: 99%
“…Hennessey's (2007) work also indicated that students who participated in a circling program were perceived by teachers to be more socially skilled and less likely to display problem behaviours. Although some authors have expressed concern about the sometimes "flimsy" evidence for effectiveness (e.g., Leach & Lewis, 2013;Lown, 2002), circling nonetheless has been described as a promising practice that provides a safe base for students to learn and practice social-emotional skills (Cefai et al, 2014).…”
mentioning
confidence: 99%